Компьютеризация технологии международного книгообмена (Библиосфера, 2010)
The article describes the possibilities of the authors' software package for automation of all technological library processes, connected with book exchange (processing orders from partners, the formation of proposals for partners, registration of receipts, sending books, etc.). The system is realized in the MS WINDOWS environment and based database management system MS SQL SERVER-2005. It is put into operation in the VGBIL.